O universo feminino e o espaço doméstico em A mão e a luva, de Machado de Assis, e O doente imaginário, de Molière - Luiz, Eloize Lemos David (2015)
The purpose of this study is to compare two classic works: the first is about the seventeenth-century in France and the other depicts the bourgeois society in nineteenth-century of Brazil, addressing the dialogue of the maids Nieta and Mrs. Oswald, in the works of Molière and Machado de Assis, which in the light of literary theory have similarities and differences, as their actions in fictional texts and along the narratives enjoy the freedom within their homes, manipulating the characters, they pursue their ideals and mainly preserve livelihoods in their domestic spaces. Although Nieta, in the play Le malade imaginaire, is one jester and Mrs. Oswald, in the novel A mão e a luva, plays the role of governess, both works have as main theme the wedding by interests and direct or indirectly the two maids contribute to the girls marry the couple, which they chose, contrary to existing social rules of those times, that thanks to the actions of these characters. Even the outgoing linguistic behavior of Nieta, the comedy of manners, makes it more active and more productive text, as the author of disagreement with the medical abuses. However, Mrs. Oswald although belonging to an updated narrative resumes Eurocentric values and the protagonist, Guiomar, breaks the romantic values, giving the novel an irreverent end, in which the young earns the right to marry with the husband, that he will ensure their upward mobility.